Study on the Quality of Economic Growth and Its Improvement Strategy in Konawe Islands Regency - Muh. Nur; Abd. Azis Muthalib; Bakhtiar Abbas; Mahmudin A. Sabilalo; Asraf Asraf (Return : Study of Management, Economic and Bussines, 2024)
This research activity will be carried out as an effort to assist the Konawe Islands Regency government in solving economic problems based on efforts to improve the quality of regional economic growth that can be achieved through strategies to improve the quality of economic growth. Especially in terms of increasing GDP growth which has implications for reducing income distribution inequality, reducing poverty rates, decreasing the unemployment rate and increasing the human development index. The purpose to be achieved in this study is to find out and analyze the quality of economic growth that occurs in Konawe Islands Regency, formulate a strategy to improve the quality of economic growth in Konawe Islands Regency. This study uses quantitative descriptive analysis and SWOT analysis. This research is expected to be able to show that improving the quality of economic growth is a form of government program preparation in order to improve the welfare of the community in Konawe Islands Regency. The results of the study show that: (1). The quality of economic growth that occurs in Konawe Islands Regency is quite quality economic growth, where the increase in the rate of economic growth has a negative direction towards reducing income distribution inequality, decreasing the percentage of population poverty and decreasing the unemployment rate, while the rate of economic growth has a positive direction towards increasing the value of the Human Development Index. (2). The strategy to improve the quality of economic growth in Konawe Islands Regency is to implement the SO (Aggressive Growth) Strategy by increasing the rate of economic growth and improving the regional economic structure by continuing to pursue regional development across sectors by utilizing regional potential with the aim of improving overall community welfare.